Demographic History and Natural Selection Regimes Shape Divergent Genomic Architectures in Two Endangered Island Oaks - Wenji Luo (4760160) (2025)
The 24 zip files contain high-quality single nucleotide polymorphisms (SNPs) called from 16 Quercus bawanglingensisand 13 Q. pseudosetulosa individuals based on whole genome resequencing data. They are in the VCF format, and were generated using the GATK software. Sample information can be found in table S1 in Supplementary Information of the manuscript. For detailed information on how the vcf files were created we refer to the Material and Methods section in the manuscript. The 12 zipped vcf files (BWL_16sample.Chr1.revhet.recode.vcf.gz - BWL_16sample.Chr12.revhet.recode.vcf.gz) contain SNPs called from the chromosomes 1-12of Q. bawanglingensis, respectively. The another 12 zipped vcf files (WSL_13sample.Chr1.revhet.recode.vcf.gz - WSL_13sample.Chr12.revhet.recode.vcf.gz) contain SNPs called from the chromosomes 1-12of Q. pseudosetulosa, respectively.